2014
DOI: 10.1111/jcpt.12203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of empiric weight-based vancomycin dosing on nephrotoxicity and mortality in geriatric patients with methicillin-resistant Staphylococcus aureus bacteraemia

Abstract: What is known and objective Few studies have evaluated the effect of vancomycin dosing on the health outcomes in geriatric patients. Data are needed to determine if higher vancomycin dosing strategies are more effective in geriatric patients and/or lead to excessive rates of adverse events. Methods This study used a subset of patients ages ≥ 65 years from a multicenter, retrospective, cohort study of methicillin resistant Staphylococcus aureus (MRSA) bacteremia. Patients received ≥ 48 hours of empiric vancom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Of 377 studies retrieved from the PubMed query and two studies retrieved from bibliographic review, only 14 studies ultimately met the criteria to be incorporated into the final analyses ( Figure 1). 8,[13][14][15][16][17][18][19][20][21][22][23][24][25] These studies were published from 2011 to 2014, with 1677 unique patients representing geriatric 19 and unspecified inpatients ( Table 1). 8,[13][14][15][16][17][18][20][21][22][23][24][25] Treatment failure was an outcome of seven studies, all of which used a definition of treatment failure that included mortality and persistent bacteremia.…”
Section: Resultsmentioning
confidence: 99%
“…Of 377 studies retrieved from the PubMed query and two studies retrieved from bibliographic review, only 14 studies ultimately met the criteria to be incorporated into the final analyses ( Figure 1). 8,[13][14][15][16][17][18][19][20][21][22][23][24][25] These studies were published from 2011 to 2014, with 1677 unique patients representing geriatric 19 and unspecified inpatients ( Table 1). 8,[13][14][15][16][17][18][20][21][22][23][24][25] Treatment failure was an outcome of seven studies, all of which used a definition of treatment failure that included mortality and persistent bacteremia.…”
Section: Resultsmentioning
confidence: 99%
“…Two retrospective studies have shown that VTC alone is not a good indicator for vancomycin treatment success among patients with MRSA bacteremia ( Jung et al, 2014 ; Makmor-Bakry et al, 2019 ). Two other retrospective cohort studies have demonstrated that VTC >15 mg/L fails to improve the outcomes of patients with MRSA infections ( Clemens et al, 2011 ; Hall et al, 2014 ). Additionally, two prospective, multicenter, observational studies have demonstrated no significant association between VTC level and vancomycin treatment response in a Chinese population diagnosed with gram-positive bacterial infections ( Liang et al, 2018 ; Shen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies have shown that VTC alone is not a good indicator for vancomycin treatment success among patients with methicillin-resistant Staphylococcus aureus (MRSA) bacteremia [7,8]. Two other retrospective cohort studies have demonstrated that VTC > 15 mg/L fails to improve the outcomes of patients with MRSA infection [17,18]. Additionally, two prospective, multicenter, observational studies have demonstrated no signi cant association between VTC level and vancomycin treatment response in a Chinese population diagnosed with gram-positive bacterial infections [11,19].…”
Section: Discussionmentioning
confidence: 99%